Effects of COVID-19 Lockdown on mental health of medical students in Lahore, Pakistan - Hassnain, Shamaila; Ahmad, Adila; Qayyum, Muhammad Saad; Farrukh, Muhammad Gulraiz; Nawaz, Usama Ahsan; Ahmad, Hadifa (Bangladesh Journal of Medical Science, 2021)
Objective: The objective isto assess the effects of lockdown on mental health of medical students of a Private medical college in Lahore. Materials and Methods: A cross sectional study has been conducted to assess the mental health status of medical students during lockdown using the designed scale DASS 21. The reliability of scale was tested using Cronbach alpha. The scale is based on 3 sub-scales used to measure depression, anxiety and stress. A sample of size 230 students from different years of MBBS is used. The data was analyzed using SPSS 21.0 Results & Discussion:The proportion of females participated in study was comparatively higher. The females were observed as more depressive. As observed 62.6% of medical students suffered from mild to very severe depression during the lockdown period.Anxiety was observed among 52% of the students. More than half dealt with various levels of anxiety and faced stress. Conclusion: COVID-19 has caused extensive distress in the lives and mental health of millions of medical students. The findings of this study indicate that depression, anxiety and stress are common morbidities amongst medical students, particularly those in their clinical training years. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.125-130